Calculation of foundation pit deformation caused by deep excavation considering influence of loading and unloading - Huang, Ming; Liu, Xing-rong; Zhang, Nai-yang; Shen, Qi-wei (Journal of Central South University, 2017)
A new analytical solution for ground surface settlement induced by deep excavation is proposed based on the elastic half space Melan’s solution, and the analytical model is related to the physical and mechanical properties of soil with the loading and unloading action during excavation process. The change law of earth pressure of the normal consolidation soil after the foundation pit excavation was analyzed, and elastic displacement calculation methods of analytic solution were further established given the influence of excavation and unloading. According to the change of stress state in the excavation process of foundation pit, the planar mechanical analysis model of the foundation excavation problem was established. By combining this model with the physical equations and geometric equations of plane strain problem with consideration of the loading and unloading modulus of soil, constitutive equation of the plane strain problem was also established. The loading and unloading modulus formula was obtained by using the parameter calculation method in Duncan-Chang curve model. The constitutive equation obtained from the model was used to calculate the soil stress state of each point to determine its loading and unloading modulus. Finally, the foundation pit displacement change after excavation was calculated, and thus the soil pressure distribution after retaining structure deformation. The theoretical results calculated by making corresponding programs were applied to engineering practice. By comparing the conventional calculation results with monitoring results, the practicability and feasibility of the calculation model were verified, which should provide a theoretical basis for similar projects.